Karakteristik HFS (High Fructose Syrup) dari umbi gembolo yang diproduksi secara hidrolisis enzimatis menggunakan amilase dan inulinase - Rezza Natori; Sri Winarti; Riski Ayu Anggreini (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
HFS (High Fructose Syrup) from gembolo tubers is an innovation in to utilize gembolo tubers which so far have not been used optimally. The purpose of this study was to determine the effect of substrate concentration and duration of saccharification on the physicochemical characteristics of HFS (High Fructose Syrup). This study used a completely randomized design (CRD) with 2 factors consisting of 9 treatment levels. The factor I was the substrate concentration (15%, 20% and 25%) and factor II was the length of saccharification (24 hours, 36 hours and 48 hours). Data were analyzed using ANOVA level 5%. If there is a difference proceed with Duncan's Test (DMRT) 5%. Based on the results of the study, the best treatment was a substrate concentration of 25% with a saccharification period of 48 hours which produced HFS with the following characteristics: yield of 18.08%; reducing sugar 41, 28%; total dissolved solids 42.00oBrix; viscosity 58.30 cP; fructose content is 14.68% and organoleptic test got the highest score.